Quantification of tumor infiltrating Foxp3+ regulatory T cells enables the identification of high-risk patients for developing synchronous cancers over upper aerodigestive tract. Issue 7 (July 2015) - Wang, Wen-Lun; Chang, Wei-Lun; Yang, Hsiao-Bai; Chang, I-Wei; Lee, Ching-Tai; Chang, Chi-Yang; Lin, Jaw-Town; Sheu, Bor-Shyang
Highlights Synchronous cancers over upper aerodigestive tract lead to poor prognosis. The tumor infiltrating Foxp3+ regulatory T cells were higher in synchronous SCC. The Foxp3+ regulatory T cell density in tumor was correlated with serum IL-10 level. The serum IL-10 level was higher in synchronous SCC than in non-synchronous ones. Foxp3+ Treg number stratifies the synchronous cancer risk for surveillance program.